Penerapan Data Mining Dalam Meningkatkan Penjualan Handphone Dengan Menggunakan Metode Algoritma Apriori (Studi Kasus: PT. Agung Sejahtera Makmur) - Fatihatul Suci; Alvino Octaviano (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Competition in business is increasingly competitive, especially from the use of mobile phones which are the main tools that can help human work. It can be seen from the various brands that are offered with interesting facilities to use and so the market for the product is getting bigger. With that, it makes business actors compete with each other with all the marketing strategies used to get lots of consumers to buy. That way a marketing strategy is needed that can help increase product sales. One of the strategies is to make product patterns that can be recommended based on office databases with the application of data mining or data mining, as well as a priori algorithm calculations and using the RapidMiner assistance application to get accurate results and can also be determined with support and confidence values. With the aim of processing transaction data that was not originally processed into data that can be used for marketing strategies. And the results of this application become an association rule, namely forming a product pattern that can help design a marketing strategy for PT. Agung Sejahtera Makmur to increase sales.